ORGANISASI KURIKULUM DALAM PENDIDIKAN AGAMA ISLAM : KAJIAN KONSEPTUAL DAN IMPLEMENTATIF - Izzah, Nailal; Ninis; Indah Rizky Aulia; Eko Nur Salim (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the nature, dimensions, factors, and types of curriculum organization in the context of education, particularly Islamic Religious Education (IRE). Curriculum organization is understood as the pattern or design of curriculum components including objectives, content, learning experiences, and assessment to achieve educational goals effectively and efficiently. This study employs a qualitative approach using the library research method, through the collection and analysis of various relevant literature. The findings indicate that curriculum organization has two main dimensions: the content dimension and the learning experience dimension, and is influenced by factors such as scope, sequence, continuity, integration, balance, and time. In addition, there are several models of curriculum organization, such as the subject-centered curriculum, the correlated curriculum, the broad-field curriculum, the integrated curriculum, and the core curriculum. Each model has its own characteristics, strengths, and weaknesses. By comprehensively understanding curriculum organization, educational institutions can design learning systems that are more focused, relevant, and adaptable to the changing times.